Hindi Version Validation of Francois-Lecompte & Roberts’ Socially Responsible Consumption Scale - Azamussan, Syed; Shanmugam, Munuswamy; Gangil, Ritu; Priya, R. (Unisia, 2024)
This study has attempted to validate the Hindi translation of Francois-Lecompte & Roberts’ (2006) socially responsible consumption (SRC) scale. This study used two translation methods: back translation and iterative procedures. A total of 10 highly professional bilingual translators were recruited to do the translation work. Five expert bilingual reviewers were appointed to review the translation work at each stage of the translation process. A five-member multidisciplinary committee was set up to adjudicate and cross-validate the final version of the translated scale. A pre-test was conducted with 21 native Hindi speakers to assess the clarity of the translated scale. A seven-member expert panel evaluated the meaning and content equivalence of the translated scale. Finally, a full psychometric test was performed with 195 responses from the target population. Factor analysis validated the Hindi translation of Francois-Lecompte & Roberts’ (2006) socially responsible consumption (SRC) scale.